Alveoloplasty and the use of osteosynthesis material in the cleft lip palate - Elena María Castilla Parrilla; Jorge Ramos Sanfiel; Belen Gironés Camarasa; Ricardo Fernández Valadés (Elsevier, 2020)
Objectives: To compare the results of secondary alveoloplasty performed in one Hospital when osteosynthesis material was used and when the bone graft does not require this material, and relating them to factors such as gender and age. Material and methods: A retrospective study was conducted from the years 2014 to 2019 in this Hospital on selected patients who met the inclusion criteria. Two periods of ages, period A: ages between 5−12 years (mixed secondary alveoloplasty) and period B: older than 12 years (late secondary alveoloplasty). Autologous bone from the iliac crest or parietal calotte was used for the bone graft. The patients were divided into 2 groups: group I: patients with alveoloplasties that required osteosynthesis material. Group II: patients who did not require osteosynthesis material. Parameters evaluated: the success criteria for alveoloplasty were assessed according to the clinical parameters described by Precious. Alveoloplasty was successful if they met all the criteria of Precious in the year of intervention. Postoperative complications in both groups were evaluated. The statistical analysis was performed using the Exact Fisher exact test for qualitative variables. Results: Alveoloplasty was successful in 89.4% of patients in group I, while it was 90.3% in group II. Alveoloplasty was successful in 87.5% of females compared to 91.17% of males. The intervention was a success in 91.48% of patients in group A, compared to 66.6% in group B. The osteosynthesis material in two patients of Group I was not degraded in the annual assessment. There were no significant differences in any of the comparisons. Conclusions: The use of osteosynthesis material does not alter the integration of the bone graft in patients that undergo alveoloplasty. Factors such as gender or age do not influence the results of the interventions. Resumen: Objetivos: Comparar los resultados de alveoloplastias secundarias realizadas en nuestro Hospital cuando utilizamos material de osteosíntesis y cuando el injerto óseo no precisa de dicho material relacionándolos con factores como el sexo y la edad. Material y métodos: Realizamos estudio retrospectivo de los años 2014-2019 en nuestro Hospital y seleccionamos los pacientes que cumplían los criterios de inclusión en nuestro estudio. Establecemos 2 grupos de edades, grupo A: edades entre 5-12 años (alveoloplastia secundaria mixta) y el grupo B: más de 12 años (alveoloplastia secundaria tardía). Para el injerto óseo se utilizó hueso autólogo procedente de cresta iliaca o calota parietal. Dividimos los pacientes en 2 grupos: grupo I: pacientes con alveoloplastias que precisaron de material de osteosíntesis. Grupo II: pacientes que no precisaron de material de osteosíntesis. Parámetros evaluados: los criterios de éxito de la alveoloplastia se valoraron según los parámetros clínicos descritos por Precious. La alveoloplastia era exitosa si cumplían todos los criterios de Precious al año de intervención. Evaluamos las complicaciones postoperatorias en ambos grupos. El análisis estadístico se realizó con el test exacto de Fisher para variables cualitativas. Resultados: El éxito de la alveoloplastia se produjo en el 89,4% de los pacientes del grupo I mientras que en el grupo II fue del 90,3%. La alveoloplastia fue exitosa en el 87,5% del sexo femenino frente al 91,17% de varones. En el 91,48% de los pacientes del grupo A la intervención fue un éxito frente al 66,6% del Grupo B. En 2 pacientes del grupo I el material de osteosíntesis no se degradó en la valoración anual. No existieron diferencias significativas en ninguna de las comparaciones. Conclusiones: La utilización de material de osteosíntesis no altera la integración del injerto óseo en pacientes a los que se realiza alveoloplastia. Factores como el sexo o la edad no influyen tampoco en los resultados de las intervenciones.